Worker voice and the health and safety regulatory system in New Zealand : an interpretivist case study inquiry in the commercial construction industry : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Palmerston North, New Zealand - Farr, Deirdre (Massey University, 2021)
The importance of involving workers in effective management of workplace health and safety (WHS) risks is well established. Transforming this rhetoric into sustainable practice continues to be a global problem. The siloed nature of industrial relations, WHS, human resource management and organisational behaviour debates has resulted in researchers talking past each other. Consequently, there is a dearth of literature drawing WHS research into contemporary debates exploring a broad range of direct and indirect forms of ‘worker voice’. The purpose of this thesis is to determine how and why the current statutory framework is contributing to enhancing workers’ involvement in workplace decisions that affect their WHS outcomes. This interpretivist constructivist multiple-case study applies a Multidisciplinary Analytical Model of Worker Voice to demonstrate how a multidisciplinary approach bridges divides and facilitates rich understanding of a contemporary phenomenon. The thesis clarifies the ambiguity and misunderstanding of terms that influence the interpretation and enactment of duties in the Health and Safety at Work Act 2015 (HSWA). It identifies and maps the different forms of worker engagement, participation and representation (EP&R) that exist under the current statutory provisions in New Zealand, and more importantly, the influence of worker voice. This research enables us to understand how and under what conditions worker EP&R can thrive. The two-phase study involved semi-structured interviews with 14 key stakeholders at the macro and industry levels, and 31 case study participants in three large commercial construction organisations at the meso level. Secondary qualitative data sources included 12 observations, and public and organisational documents. Hermeneutic analysis and interpretation revealed how the current HSWA stimulated improvements in leadership and risk management. The characteristics of effective worker voice systems were co-constructed with the key stakeholders and developed into an EP&R Compliance Maturity Model of Worker Voice. This model highlighted proactive and reactive responses to the HSWA in the organisations operating in a low-union, high-risk context. The overarching perceptions of the HSWA reinvigorating interest in worker voice underpinned improvements in macro level tripartism and meso level engagement. However, traditional representation structures have been eroded rather than strengthened.
Figures 2.1 and 3.2 are re-used with permission.
Keywords: New Zealand. Health and Safety at Work Act 2015; Industrial hygiene; Industrial safety; Law and legislation; Construction industry; Employees; Health and hygiene; Management; Employee participation; New Zealand; 350505 Occupational and workplace health and safety